PENGUJIAN KESETARAAN PRESISI DAN SKALA UKUR BUTIR-BUTIR PADA SKALA PSIKOLOGI - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this study is to identify the measuremenmt odels that appropriate to measure psychologicaal ttributes toward psychological scale M easuremenmt odels that includesisparallel,tau-equivalenatndkonjenerikmodel.Each model has different as sumptions according to eachitemsprecisionandscalemeasuringon psychological scale.As a sampleofpsychological scalethis studyusesChildDepressionInventory (CDI) andRosenbergSelf-EsteemScale. Data takenfrom the 3.183 adolescentsfrom junior and senior high school with age rangefrom 15 to 19 years in DIY. Bothscaleis tested using the Hotelling T2 test for testing the equalityofmeanandvarianceandconfirmatory factor analysisthroughstructural equationmodelingto test thegoodnessfit of themodel.This studyfound that psychological scalestendtofit with congenericmodelthan thers. Congenericmodel asone of measurements model that assumeseveryitemsin a scalehasa differentprecisionand scaleof measure.Therefore,it is concludedthat itemsin themeasurementstendtobemeasuredin psychological attributesto differentamountofmeasure. Keywords: measurementmodel, psychological scale, items precision and scalemeasure